(untitled) (Biological Sciences - PJSIR, 2001)
Modification of gelatin by grafting with methyl methacrylate i n the presence of potassium persulphate was studied and the results were discussed with respect to grafting ratio (GR) grafting efficiency (GE), rate of grafting (Rg) and rate of conversion of monomer (Rp). The lower concentration of gelatin favours more grafting. Homopol ymerization of monomer is not observed in most of the cases.